(untitled) (International Journal of Engineering and Computer Science, 2014)
Due to the fact that reliable and sustainable electricity supply has been regarded as essential for economic development, Renewable energy resources are a favorable alternative for energy supply. Commonly Renewable energy systems use solar, wind, and hydro energy sources In order to handle their fluctuating nature, these sources can be integrated together. These systems use different energy generators in combination, by this maintaining a stable energy supply in times of shortages of one the energy resources. For instance, winds are usually relatively strong in winter and solar radiation is higher in summer. A balanced system provides stable outputs from sources such as these and minimizes the dependence of the output upon seasonal changes Main hope attributed to these systems is their good potential for economic development.